Production Performance of African Catfish (Clarias gariepinus, burch) were Rearing with Biofloc technology - Sri Hastuti; Subandiyono Subandiyono (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2014)
Exploratory research to measure biological variables consisting of feed intake, feed utilization efficiency, feed conversion ratio (FCR), growth and survival of fish was done in the field, in Comal, Pemalang . The aims of the research were to assess the performance of the production as well as to assess the dynamics of the water quality and feed utilization efiiensi catfish (Clarias gariepinus, Burch) cultivated with biofloc technology.  The trial fish were reared in cement tanks at the density of 1,000 fish/m2. During maintenance periode, the fish were fed on the artificial diet containing protein of 30%, fat of 5%, fiber of 6%, mineral mix of 13%, and water of 13%. The trial feed was given by applying  ad satiation methode.  The data optain were analyzed descriptively, based on the tables, histograms, and charts provided. Water quality parameters were measured in every 2 weeks along the maintenance period. This study indicated that biofloc technology applied in the catfish (C. gariepinus) farming was able to increase the fish production, improve the feed utilization efficiency, and reduced feed conversion rate. This technology was also able to improve the water quality and increase the survivors of the trial fish. By Applying biofloc technology could support  the catfish life until the density  of 1,000 fish/m2. Keywords : catfish, biofloc, production, growth, feed, efficiency